Prevalence and socio-demographic correlates of active commuting to school in a nationwide representative sample of German adolescents - Reimers, Anne Kerstin; Jekauc, Darko; Peterhans, Eliane; Wagner, Matthias; Woll, Alexander (Preventive Medicine, 2013)
Objective. To assess the prevalence and socio-demographic correlates of walking and cycling to school in a nationwide representative cross-sectional sample of German adolescents. Methods. A sample of 1828 German adolescents aged 11–17 years were examined between 2003 and 2006. Mode of commuting to school was assessed using a reliable self-report measure. Socioeconomic status, migration background and residential area were assessed as socio-demographic variables using a parent-report question- naire. Results. Overall, 19.4% of adolescents walked and 22.2% cycled to school. Compared to girls with high socio- economic status, girls with low socioeconomic status were more likely to walk (OR=1.89, 95% CI=1.23–2.89). Migration background increased the chance of walking in girls (OR = 0.47, 95% CI = 0.32–0.70) and decreased the chance of cycling in boys (OR=2.39, 95% CI=1.35–4.24). Compared to living in cities, living in rural areas lowered the chance of walking (girls: OR=0.29, 95% CI=0.18–0.50; boys: OR=0.54, 95% CI= 0.32–0.93) and cycling (girls: OR=0.12, 95% CI=0.06–0.24; boys: OR=0.34, 95% CI=0.21–0.56), and living in medium-sized towns increased the chance of cycling in girls (OR=1.86, 95% CI=1.24–2.78) and boys (OR=1.75, 95% CI=1.20–2.56), respectively. Conclusions. In Germany many adolescents use motorised transportation. Socio-demographic variables were associated with mode of commuting.
Keywords: Walking; Transportation; Adolescent; Germany; Schools; Social class; Health surveys